International Relations’ Critical Turn in the Humanitarian Space: Opportunities for Christian Engagement - Moore, Alana (International journal of public theology, 2020)
Abstract International Relations scholars routinely credit Christian actors with helping to create the modern international humanitarian order by institutionalizing principles of care and assistance within global governance. As this humanitarian order has become more secularized, however, faith-based reflections have been sidelined in secular academic work on humanitarian issues. This article reflects on the opportunities for dialogue and mutual engagement following the critical turn in International Relations scholarship over recent years. It highlights the development of International Relations thinking on the normative dimensions of the international humanitarian order and shows how their critiques of a secular order have created a window for engagement with the intellectual resources of the Christian traditions. Developing meeting places for engaging on deeper questions of ontologies of practice provides an opportunity to pursue a richer vision of global humanitarian endeavours, to the benefit of all.